Impact of practice settings on knowledge, attitude, and practice of disposal of unwanted pharmaceuticals among pharmacists in a selected city of Tamil Nadu - Siva Shree Rajagopalan Suresh Babu, Saranya Subbaiah, Sarang Paniot, Shivani Ramesh, Vanitha Rani Nagasubramanian (Journal of Applied Pharmaceutical Science, 2021)
A cross-sectional study was conducted among 86 hospital pharmacists of a tertiary care university hospital and 86 community pharmacists in the metropolitan city in Tamil Nadu to assess the impact of practice settings on their knowledge, attitude, and practice of safe disposal of expired and unwanted medicines. A 19-item validated questionnaire was administered to the study subjects, and their responses were analyzed statistically. Around 65% of the hospital pharmacists and only 30% of community pharmacists stated returning drugs to the source as the best method of unwanted drug disposal. 67% of the hospital pharmacists were aware of the environmental hazards caused by improper disposal of medicines, but only 32% of community pharmacists were aware of the same. 88% of the hospital pharmacists accepted the use of collection boxes and display of posters on safe disposal in the pharmacies and both consented to participate in educational programs focusing on safe disposal of medicines. Pharmacists practicing in the hospital pharmacy setting had significantly better knowledge and attitude on safe disposal of unwanted medicines than those practicing in the community. Continuous educational interventions and awareness workshops for the community pharmacists on safe medication disposal is the need of the hour.
Keywords: Unwanted medicines, safe disposal, practice settings, pharmacists, knowledge, attitude, practice